ANÃLISIS DE INDICADORES PARA EL FORTALECIMIENTO DEL PROGRAMA EDUCATIVO DE LA MAESTRÃA EN ADMINISTRACIÃ“N DE NEGOCIOS DEL CENTRO UNIVERSITARIO DE LA COSTA - DÃaz, Luz Amparo Delgado; Bizarrón, Manuel Ernesto Becerra; Ballesteros, Georgina Dolores Sandoval (European Scientific Journal, ESJ, 2015)
Quality of higher education in Mexico has been a priority for government and higher education institutions. In search of continuous improvement and quality assurance within the public higher education subsystem, the goverment has encouraged a participatory strategic planning exercise, in higher education institutions in order to promote the quality of higher education. University of Guadalajara, is the second largest public university in México, this paper presents an analysis of the context and indicators of one of its programs, the Masters in Business Administration offered at the Coast campus of the University of Guadalajara. The analysis includes different approaches of authors that address the context and indicators to improve quality in higer education and its processes, it also identifies the contributions of the MBA program